The Effectiveness of Using Pop-Up Book Media in Thematic Learning Reviewed from Learning Outcomes - Annisa Salsabila (Jurnal Wawasan Sarjana, 2024)
The purpose of this research was to determine the effectiveness of using Pop-Up Book Media in thematic learning at Madrasah Ibtidaiyah Asy-Syafi’iyah grade III. This research is using quantitative research with pre-experemintal methods. The research design is One Group-Pretest-Posttest Only. Population in this research were all the student of class III Madrasah Ibtidaiyah Asy-Syafi’iyah and then the population was selected using probability sampling techniques with cluster sampling type. Data of learning outcomes was obtanied by Pretest-Posttest in a multiple choice form. The result of this research is average of pretest score is 77,27 while average of posttest score is 93,18 with an average N-Gain is 0,69 with a medium category. Pop-Up Book Media has succeeded in improving learning outcomes of grade III Madrasah Ibtidaiyah Asy-Syafi’iyah. This is proven by the hypothesis test results which show that the Sig. (2-Tailed.) value is 0.000 < 0.05. Therefore, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted.